Effect of heat and thermosonication on kinetics of peroxidase inactivation and vitamin C degradation in seedless guava (Psidium guajava L.) - Ganjloo, Ali; Abdul Rahman, Russly; Bakar, Jamilah; Osman, Azizah; B., Mandana (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
This study aims to evaluate the effect of heat and the simultaneous application of heat (80-95°C) and ultrasonic waves (thermosonication) on the inactivation kinetic of peroxidase and vitamin C degradation in seedless guava. Ultrasonic wave’s amplitudes except 25 and 100% had significant (P<0.05) effect on peroxidase inactivation rate. The thermal and thermosonication inactivation of peroxidase was described well by first-order kinetics (R2>0.98). In the heat blanching process, the peroxidase inactivation rate constant increased from 1.1×10-2 to 4.6×10-2 s-1. However, the inactivation rate of peroxidase was increased by 1.5–3 times in the temperature range 80–95ºC, with the 50 and 75% ultrasonic wave amplitudes, respectively. Decreases in vitamin C contents due to blanching treatments were found. Blanching processes at high temperature and short time resulted in higher vitamin C retention. It was found that thermosonication treatment inactivates seedless guava peroxidase at less severe blanching conditions and consequently retains vitamin C content at higher levels. The present findings will help to design the blanching conditions in order to reduce the severity of conventional thermal treatments and, therefore, improving the quality of the thermally treated product.